Where Are All the Women? Gender Bias Persists in Social Studies Texts - Tim Fry; Brenna S. Hofelt (The Advocate, 2012)
Introduction: Creating an inclusive and a more equitable classroom is a goal that all educators should continually strive for. One area of concern is that many girls and young women do not see themselves in curriculum materials - especially in the social studies.